Plant Cell Culture - Dixon, R. A;Ed. Gonzales, Robert A;Ed (Practical approach series, 145., 1994)
Plant cell culture techniques are being increasingly used in basic research and for plant exploitation in industry (genetic engineering, micropropagation). In this book, internationally recognized experts describe the techniques in use in their laboratories for isolating and manipulating cell cultures, and their central importance in plant biotechnology.